Die uitbouing van die Bybelse kanon in antieke Judaïsme en die vroeë Christendom - Frey, Jörg (HTS teologiese studies, 2015)
The development of the biblical canon in ancient Judaism and early Christianity. A brief account of the process of the development of both the Jewish and the bipartite Christian canon is given. It is argued that due to insights gained from recent textual discoveries, especially the Dead Sea Scrolls (Qumran texts), earlier theories about the history of canonisation had to be reviewed. With the New Testament canon the authors focus on the influence of Marcion as well as the various other factors that played a role in the process of canonisation. It is shown that canonisation was the result of a complicated and variegated canonical process. But in spite of the problems of the criteria used and other factors involved, the biblical canon is theologically valuable and ‘well-chosen’.